Silent ovarian ectopic pregnancy: a case report - Rafiq, Sophia; Shakeel, Shazia; Tanveer, Neha; Pervaiz, Zainab; Khan, Taleah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
In clinical practice, an ovarian pregnancy is considered one of the most challenging diagnoses faced by an obstetrician/gynecologist. In this article, we report a 31-year-old Asian-Pakistani female, who presented to the ObsGynae clinic with 8 weeks of amenorrhea, a positive urine pregnancy test, and very high serum β-hCG levels. Transvaginal ultrasonography ruled out a tubal pregnancy, and the patient was sent for repeat β-hCG levels. The patient was hemodynamically stable and displayed no characteristic signs and symptoms of an ectopic pregnancy. Upon repeat scans and β-hCG levels, a diagnosis of ovarian ectopic pregnancy was made. The patient was managed on medication; a single dose of I/M 50 mg/m2 methotrexate was administered and the resultant decline in β-hCG levels proved the success of conservative treatment in this case. An ovarian ectopic can present as a life-threatening condition, and a high index of suspicion can prevent morbidity as well as mortality. Ovarian pregnancy, without any alarming signs despite very high β-hCG levels, as reported in this case, is one of the rarest clinical cases observed.